Active shape models with adaptive weights - Mandziy, T.S. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2009)
Improvement of active shape models dealing with noisy and blured images of objects is developed. Results are tested on a set of radiographic images of welds. Improvement of performance of the proposed modified active shape models for radiographic images compared to conventional ones was shown basing on experimental results comparison.